Pengembangan Model Capacitated Maximal Covering Location Problem (CMCLP) untuk Penentuan Lokasi dan Tipe Distribution Center - Santoso Santoso; Rainisa Maini Heryanto (OPSI, 2022)
Facility location decision making is necessary for both the public and private sectors for optimum utilization of resources. While the private sector may locate facilities to maximize profit or minimize cost, the public sector aims at providing services to cover as many in the population as possible. In this research, a Capacitated Maximal Covering Location problem (CMCLP) with constraints in actual world such as various types of facilities and consider maximum available budget to build the facilities. An Mixed Integer Linear Programming (MILP) model is constructed in order to find the optimal solution. The problem to be solved is determining the strategic location for establishment of a Distribution Center (DC) that maximize number of demands that can be fulfilled. A numerical example in the previous study will be used and solved using MATLAB 9.0. From the development model, the company finds the optimal location to build a DC and knows the number of products allocated from DC to each demand point and the maximum number of demands that could be fulfilled as in the previous study. The company also could find out the type of DC to be built and of course meet the available budget to build the DC.